Lithium manganese iron phosphate positive electrode material and preparation method thereof

By using viscous dispersants and composite carbon sources in the preparation process of lithium manganese iron phosphate positive electrode materials, the problem of improving the electrochemical performance of lithium manganese iron phosphate positive electrode materials is solved, and higher conductivity and electrochemical performance are achieved.

CN119480997APending Publication Date: 2025-02-18HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411642449.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

How to improve the electrochemical performance of lithium manganese iron phosphate positive electrode material.

Method used

By adding a viscous dispersant and a composite carbon source in the preparation process of lithium manganese iron phosphate positive electrode material, the dispersion of the material and the uniformity of the carbon encapsulation layer are improved, and its conductive and electrochemical properties are improved.

Benefits of technology

The electrochemical performance of lithium manganese iron phosphate cathode material, including lower charge transfer resistance and higher capacity retention, has significantly improved its performance in electric vehicle power batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480997A_ABST
    Figure CN119480997A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium manganese iron phosphate positive electrode material and a preparation method thereof, and relates to the technical field of lithium ion batteries, and the method comprises the following steps: adding a LiMnXFe (1-X) PO4 precursor, a composite carbon source and a part of viscous dispersant into deionized water according to a ratio, carrying out ultrasonic oscillation for 1-2 hours, and then carrying out suction filtration, drying and grinding to obtain a mixture; putting the mixture into a sintering furnace, sintering for 2 hours at 200 DEG C in a nitrogen atmosphere, heating to 650-750 DEG C, sintering for 4-5 hours, cooling to room temperature, and grinding to obtain modified LiMnXFe (1-X) PO4; and uniformly mixing the modified LiMnXFe (1-X) PO4, the conductive agent, the binder and the residual viscous dispersant to obtain black slurry, namely the lithium iron manganese phosphate positive electrode material with excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium iron manganese phosphate positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid growth of new energy vehicles and energy storage, as well as the acceleration of overseas lithium battery capacity construction, the market demand for lithium-ion batteries will continue to grow. Lithium-ion batteries are a type of secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive and negative electrodes to work in a cyclic charging and discharging process. During the charging and discharging process, Li + The Li is inserted and deintercalated back and forth between the two electrodes. + The electrolyte is then embedded in the negative electrode after being extracted from the positive electrode, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. This process mainly relies on the various components inside the battery to complete the conversion between electrical energy and chemical energy. With the continuous emergence of new materials and new processes, the performance of lithium-ion batteries is also constantly improving.

[0003] There are many studies on positive electrode materials for lithium-ion batteries, including positive electrode materials with layered, spinel, olivine and other structures. In the existing technology, researchers have also combined the advantages of positive electrode materials with different structures to synthesize a mixed solid solution of lithium iron phosphate and lithium manganese phosphate, namely lithium manganese iron phosphate positive electrode material, which has more complete and excellent performance.

[0004] As the world pays more attention to environmental protection and sustainable development, the electric vehicle market is expanding rapidly. As a new generation of lithium battery cathode material, lithium iron manganese phosphate has the advantages of high energy density, low cost, long life and good safety, and is very suitable for electric vehicle power batteries. Therefore, with the continuous growth of the electric vehicle market, the demand for lithium iron manganese phosphate cathode materials is also increasing, and the requirements for its electrochemical performance are also getting higher and higher. Summary of the invention

[0005] The purpose of the present invention is to provide a lithium manganese iron phosphate positive electrode material and a preparation method thereof to solve the following technical problems:

[0006] How to improve the electrochemical performance of lithium manganese iron phosphate positive electrode materials.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] In a first aspect, the present invention discloses a lithium manganese iron phosphate positive electrode material, comprising the following components in parts by weight: 95-100 parts Li Mn X Fe (1-X) PO 4Precursor, composite carbon source 5-8 parts, conductive agent 1-2 parts, binder 0.2-0.8 parts, viscous dispersant 0.5-1 parts;

[0009] Preferably, LiMn X Fe (1-X) PO 4 The precursor is 98 parts, the composite carbon source is 6 parts, the conductive agent is 1.5 parts, the binder is 0.5 parts, and the viscous dispersant is 1.5 parts.

[0010] Furthermore, the preparation method of the viscous dispersant is:

[0011] Oleic acid is dissolved in anhydrous ethanol to form an oleic acid ethanol solution, sodium hydroxide ethanol solution is added dropwise to the oleic acid ethanol solution for neutralization reaction, phenolphthalein is added as an indicator, and the dropping is stopped immediately when the solution changes from colorless to light red, and then heated at 80-100°C for 2-3h to remove ethanol and water, and the obtained precipitate is transferred to an ethanol-ether mixed solution and stirred for 2-3h, wherein the volume amount of ethanol and ether in the ethanol-ether mixed solution is the same; after the stirring is completed, it is first filtered through a suction filter, and then repeatedly washed with deionized water for 3-5 times, and then transferred to a vacuum drying oven to dry at 120°C for 2h, and then added to a grinder for grinding for 2-3h, and finally a nano-scale powdered viscous dispersant is obtained.

[0012] Furthermore, the mass fraction of oleic acid in the oleic acid ethanol solution is 10%, and the concentration of the sodium hydroxide ethanol solution is 0.5 mol / L.

[0013] The viscous dispersant prepared by the above method is light yellow. In order to avoid its oxidation and deterioration, it needs to be sealed and stored for a period of time after preparation and before it is put into use. After the viscous dispersant is dissolved in water, it is partially hydrolyzed into insoluble acid soap and sodium hydroxide, causing the liquid to become emulsified and have a certain viscosity. At the same time, as an anionic surfactant, it has a hydrophilic group (carboxyl group) and a hydrophobic group (carbon chain). This structure enables it to form a molecular film in water or an organic solvent and change the surface tension of the solution.

[0014] Furthermore, the LiMn X Fe (1-X) PO 4 The raw materials for preparing the precursor include a lithium source, a manganese source, an iron source, and a phosphorus source, wherein the value of X is 0.6-0.8, and preferably, X=0.6.

[0015] Furthermore, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate. Preferably, the lithium source is lithium carbonate.

[0016] The manganese source includes manganese oxide (MnO2 、MnO 3 、MnO 7 ), manganese salts (MnC 2 O 4 、MnSO 4 、Mn(NO 3 ) 2 etc.), preferably, the manganese source is MnC2O4.

[0017] The iron source includes iron oxides (FeO, Fe 2 O 3 , Fe 3 O 4 ), iron salts (FeCl 3 , Fe 2 (SO 4 ) 3 、Fe(NO 3 ) 3 ), preferably, the iron source is FeCl 3 .

[0018] The phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and ammonium dihydrogen phosphate; preferably, the phosphorus source is phosphoric acid.

[0019] Furthermore, the LiMn X Fe (1-X) PO 4 The preparation method of the precursor is:

[0020] According to LiMn X Fe (1-X) PO 4 The lithium source, manganese source, iron source, phosphorus source and deionized water are weighed in a chemical molar ratio and put into a grinder for full grinding. The slurry is taken out and placed in a spray dryer for spray granulation to obtain LiMn X Fe (1-X) PO 4 Precursor.

[0021] Furthermore, the composite carbon source includes polyvinyl alcohol (PVA) and polyacrylonitrile (PAN) in a mass ratio of 5:2; when polyvinyl alcohol is used as a carbon source, carbonization products can be generated during the pyrolysis process, and then in LiMn X Fe (1-X) PO 4 A carbon coating is formed on the surface, which not only improves the conductivity of the material, but also prevents the agglomeration of particles, thereby improving the electrochemical properties of the material to a certain extent.

[0022] However, when PVA is used alone as a carbon source, its decomposition temperature is relatively low and it begins to decompose at 200 °C. As the decomposition proceeds, X Fe (1-X) PO 4 In this process, the distribution and conversion of the intermediate products are extremely difficult to control, so the thickness uniformity of the carbon coating layer is difficult to ensure; therefore, the present invention uses PVA as the carbon source and adds PAN as the carbon source. The decomposition temperature of PAN is higher than that of PVA, and its carbonization time is later than that of PVA. PVA first reacts with Li Mn X Fe (1-X) PO 4 A non-uniform carbon coating is formed on the surface. The surface of the carbon coating is rough and has many pits. After PAN is carbonized, the carbonized material is carried to the pits by the gas generated during the decomposition process, thereby compensating the pits and making the non-uniform carbon coating uniform and smooth, which can improve the Li Mn X Fe (1-X) PO 4 Carbon wrapping surface treatment performance.

[0023] Furthermore, the conductive agent is Super-P.

[0024] Furthermore, the binder is polyvinylidene fluoride.

[0025] In a second aspect, the present invention further discloses a method for preparing the lithium manganese iron phosphate positive electrode material as described above, characterized in that it comprises the following steps:

[0026] S1: Li Mn X Fe (1-X) PO 4 The precursor, the composite carbon source and part of the viscous dispersant are added to deionized water in proportion and ultrasonically vibrated for 1-2 hours, and then filtered, dried and ground to obtain a mixture; the hydrophobic groups in the viscous dispersant are adsorbed on the LiMn X Fe (1-X) PO 4 The hydrophilic groups on the surface of the precursor and carbon source are oriented toward the deionized water, thus increasing the LiMn X Fe (1-X) PO 4 The dispersion of the precursor in deionized water makes the obtained mixture more homogeneous.

[0027] S2: Place the mixed material in a sintering furnace, first sinter at 200℃ for 2h in a nitrogen atmosphere, then heat to 650-750℃ for 4-5h, cool to room temperature and grind to obtain modified LiMn X Fe(1-X) PO 4 ;

[0028] S3: Modified LiMn X Fe (1-X) PO 4 , conductive agent, binder and the remaining viscous dispersant are mixed evenly, and the obtained black slurry is the lithium manganese iron phosphate positive electrode material; in this process, the viscous dispersant is used to promote the LiMn X Fe (1-X) PO 4 On the other hand, the uniformity of dispersion in the slurry can replace part of the binder to play a bonding role, thereby reducing the amount of binder used, increasing the proportion of active substances in the positive electrode material, and thus improving its electrochemical performance.

[0029] Furthermore, the usage ratio of the viscous dispersant in step S1 and step S3 is 3:2.

[0030] Beneficial effects of the present invention:

[0031] (1) LiMn in the lithium manganese iron phosphate positive electrode material of the present invention X Fe (1-X) PO 4 During the preparation process, a viscous dispersant was added to obtain modified LiMn X Fe (1-X) PO 4 The hydrophobic groups in the viscous dispersant are adsorbed on the LiMn X Fe (1-X) PO 4 The hydrophilic groups on the surface of the precursor and carbon source are oriented toward the deionized water, thus increasing the LiMn X Fe (1-X) PO 4 The dispersion of the precursor in deionized water makes the obtained mixture more homogeneous, thereby improving the LiMn X Fe (1-X) PO 4 functionality, thereby improving its electrochemical performance.

[0032] (2) The viscous dispersant in the lithium manganese iron phosphate positive electrode material of the present invention is added twice, the first time in the preparation of the modified LiMn X Fe (1-X) PO 4 The purpose of adding in the process is to obtain a homogeneous LiMn X Fe (1-X) PO 4 The second time is when the positive electrode material (black slurry) is added, the purpose is to promote the modification of LiMnX Fe (1-X) PO 4 While improving the uniformity of dispersion in the slurry, it also replaces part of the binder to play a bonding role, thereby reducing the amount of binder used, increasing the proportion of active substances in the positive electrode material, and thus improving its electrochemical performance.

[0033] (3) LiMn in the lithium manganese iron phosphate positive electrode material of the present invention X Fe (1-X) PO 4 The carbon source is a composite carbon source formed by blending PVA and PAN. The decomposition temperature of PAN is higher than that of PVA, and its carbonization time is later than that of PVA. PVA first reacts with LiMn X Fe (1-X) PO 4 A non-uniform carbon coating is formed on the surface. The surface of the carbon coating is rough and has many pits. After PAN is carbonized, the carbonized material is carried to the pits by the gas generated during the decomposition process, thereby compensating the pits and making the non-uniform carbon coating uniform and smooth, which can improve the Li Mn X Fe (1-X) PO 4 The carbon-wrapped surface treatment performance can improve its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present invention will be further described below in conjunction with the accompanying drawings.

[0035] Figure 1 The modified LiMn prepared in Example 1 of the present invention 0.6 Fe 0.4 PO 4 Electron microscopic morphology of

[0036] Figure 2 The modified LiMn prepared in Example 2 of the present invention 0.6 Fe 0.4 PO 4 Electron microscopic morphology of

[0037] Figure 3 The modified LiMn prepared in Example 3 of the present invention 0.6 Fe 0.4 PO 4 Electron microscopic morphology of

[0038] Figure 4 It is LiMn obtained in Comparative Example 1 of the present invention. 0.6 Fe 0.4 PO 4 Electron microscopic morphology of

[0039] Figure 5 It is LiMn obtained in Comparative Example 2 of the present invention. 0.6 Fe 0.4 PO 4 Electron micrograph of . DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0042] Preparation Example 1

[0043] Preparation of LiMn 0.6 Fe 0.4 PO 4 Precursor.

[0044] Lithium carbonate (Li) was weighed according to the molar mass ratio of 5:3:2:5. 2 CO 3 ), manganese carbonate (MnCO 3 ), ferric chloride (FeCl 3 ), phosphoric acid (H 3 PO 4 ) and an equal amount of deionized water were put into a grinder and fully ground. After taking out the slurry, the same amount of deionized water was added to dilute it evenly, and then placed in a spray dryer for spray granulation at a speed of 60 mL / min to obtain LiMn 0.6 Fe 0.4 PO 4 Precursor.

[0045] Preparation Example 2

[0046] Preparation of composite carbon source.

[0047] 10g PVA, 4g PAN and 15g deionized water were added into a ball mill (the ball-to-material ratio was 5:1, and the grinding balls were zirconia balls) and ground for 1.5h. After grinding, the material was taken out, placed in a vacuum drying oven and dried at 100°C for 30min, and then transferred to a resonance mixer for vibration separation. After grinding, a powdered composite carbon source was obtained.

[0048] Preparation Example 3

[0049] Preparation of viscous dispersions.

[0050] Add 180g of anhydrous ethanol to a beaker with a capacity of 300mL, then add 20g of oleic acid and stir evenly to form an oleic acid ethanol solution, add 0.5g of phenolphthalein to the oleic acid ethanol solution, and then slowly drop a sodium hydroxide solution with a concentration of 0.5mol / L to the oleic acid ethanol solution, stirring while dropping until the solution changes from colorless to light red, and immediately stop dropping; place the beaker on an electric hot plate and heat it at 90°C for 2.5h to evaporate ethanol and water to obtain a precipitate, add an ethanol-ether mixed solution (ethanol to ether mass ratio of 1:1) to the beaker to cover more than twice the thickness of the precipitate, stir for 2.5h, transfer to a suction filter for filtration, then wash repeatedly with deionized water 4 times, then transfer to a vacuum drying oven to dry at 120°C for 2h, then add to a grinder for grinding for 2.5h, and finally obtain a nanometer-level powdered viscous dispersant.

[0051] Example 1

[0052] Preparation of lithium manganese iron phosphate positive electrode material.

[0053] Step 1: 95 g of LiMn prepared in Preparation Example 1 0.6 Fe 0.4 PO 4 The precursor, 5 g of the composite carbon source prepared in Preparation Example 2 and 0.8 g of the viscous dispersant prepared in Preparation Example 3 were added to deionized water in proportion and ultrasonically vibrated for 1 h, and then filtered, dried and ground to obtain a mixture;

[0054] Step 2: Place the mixture in a sintering furnace, sinter at 200°C for 2h in a nitrogen atmosphere, then heat to 650°C for 5h, cool to room temperature and grind to obtain modified LiMn 0.6 Fe 0.4 PO 4 ;

[0055] Step 3: Modify LiMn 0.6 Fe 0.4 PO 4 , 1g Super-P, 0.2g polyvinylidene fluoride and 0.4g viscous dispersant prepared in Preparation Example 3 are mixed evenly to obtain a black slurry that is the lithium manganese iron phosphate positive electrode material.

[0056] Example 2

[0057] Preparation of lithium manganese iron phosphate positive electrode material.

[0058] Step 1: 98 g of LiMn prepared in Preparation Example 1 0.6 Fe0.4 PO 4 The precursor, 6 g of the composite carbon source prepared in Preparation Example 2 and 1 g of the viscous dispersant prepared in Preparation Example 3 were added to deionized water in proportion, ultrasonically vibrated for 1.5 h, and then filtered, dried and ground to obtain a mixture;

[0059] Step 2: Place the mixture in a sintering furnace, first sinter at 200°C for 2h in a nitrogen atmosphere, then heat to 700°C for 4.5h, cool to room temperature and grind to obtain modified LiMn 0.6 Fe 0.4 PO 4 ;

[0060] Step 3: Modify LiMn 0.6 Fe 0.4 PO 4 , 1.5 g Super-P, 0.5 g polyvinylidene fluoride and 0.5 g of the viscous dispersant prepared in Preparation Example 3 are mixed evenly to obtain a black slurry that is the lithium manganese iron phosphate positive electrode material.

[0061] Example 3

[0062] Preparation of lithium manganese iron phosphate positive electrode material.

[0063] Step 1: 100 g of LiMn prepared in Preparation Example 1 0.6 Fe 0.4 PO 4 The precursor, 8 g of the composite carbon source prepared in Preparation Example 2 and 1.2 g of the viscous dispersant prepared in Preparation Example 3 were added to deionized water in proportion and ultrasonically vibrated for 2 h, and then filtered, dried and ground to obtain a mixture;

[0064] Step 2: Place the mixture in a sintering furnace, sinter at 200°C for 2h in a nitrogen atmosphere, then heat to 750°C for 4h, cool to room temperature and grind to obtain modified LiMn 0.6 Fe 0.4 PO 4 ;

[0065] Step 3: Modify LiMn 0.6 Fe 0.4 PO 4 , 2g Super-P, 0.8g polyvinylidene fluoride and 0.5g viscous dispersant prepared in Preparation Example 3 are mixed evenly to obtain a black slurry that is the lithium manganese iron phosphate positive electrode material.

[0066] Comparative Example 1

[0067] Compared with Example 2, the only difference is that the viscous dispersant prepared in Preparation Example 3 is not added in step 1, and the other steps and conditions are exactly the same, and finally a black slurry-like lithium manganese iron phosphate positive electrode material is obtained.

[0068] Comparative Example 2

[0069] Compared with Example 2, the only difference is that in step 1, the composite carbon source prepared in Preparation Example 2 is replaced by PVA, and the other steps and conditions are exactly the same, and finally a black slurry-like lithium manganese iron phosphate positive electrode material is obtained.

[0070] The powdered LiMn obtained in step 2 of the preparation process of Example 1-3 and Comparative Example 1-2 0.6 Fe 0.4 PO 4 Scanning electron microscopy was used to obtain the corresponding Figure 1-5 The morphology of Figure 1-3 It can be seen that the modified LiMn 0.6 Fe 0.4 PO 4 The micron-shaped spherical particles are more uniform in size and have a smoother surface. Figure 4 It can be seen that the LiMn 0.6 Fe 0.4 PO 4 There are more agglomerations between the micron-shaped spherical particles. The size of the micron-shaped spherical particles is uneven, but the surface is still smooth, which shows that the increase of viscous dispersant can promote the 0.6 Fe 0.4 PO 4 The particle size is uniform; Figure 5 It can be seen that the LiMn 0.6 Fe 0.4 PO 4 The size of the micron-shaped spherical particles is still uniform, but the surface is relatively rough, which shows that the use of composite carbon sources can enhance the uniformity of carbon encapsulation.

[0071] Comparative Example 3

[0072] Compared with Example 2, the only difference is that in step three, the viscous dispersant prepared in Preparation Example 3 is replaced by polyvinylidene fluoride, and the other steps and conditions are exactly the same, and finally a black slurry-like lithium manganese iron phosphate positive electrode material is obtained.

[0073] The black slurry-like lithium manganese iron phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-3 were respectively made into batteries, and the production method was as follows: put the aluminum foil into a coating machine, pour the black slurry, and transfer it into an oven to dry at 40°C for 4 hours after evenly coating it. Then, put the dried aluminum foil into a punching machine, punch out a number of pole pieces containing active substances, weigh them, put the pole pieces in a drying bottle, transfer them to a vacuum drying oven and dry them at 110°C for 6 hours, and finally assemble them into button batteries in a vacuum glove box.

[0074] Then, the prepared button battery was subjected to electrochemical performance tests, the charge transfer resistance was tested using an electrochemical workstation, and the capacity retention rate was tested using a cyclic voltammetry test method, and the test results are listed in Table 1. Table 1 is as follows:

[0075] Table 1

[0076]

[0077]

[0078] By analyzing the data in Table 1, it can be seen that the battery made of the lithium iron manganese phosphate positive electrode material obtained in Examples 1-3 has a significantly lower charge transfer resistance than that of Comparative Examples 1-3, which indicates that its electron migration rate is faster, while the capacity is significantly higher, which indicates that its rate performance is better; based on this, it can be seen that the lithium iron manganese phosphate positive electrode material of the present invention has stronger electrochemical properties.

[0079] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: The following components are included in weight: 95-100 parts LiMn X Fe (1-X) PO4 precursor, 5-8 parts of composite carbon source, 1-2 parts of conductive agent, 0.2-0.8 parts of binder, 1.2-1.8 parts of viscous dispersant; Wherein, the preparation method of the viscous dispersant is: Dissolve oleic acid in anhydrous ethanol to form an oleic acid ethanol solution, add sodium hydroxide ethanol solution to the oleic acid ethanol solution for neutralization, add phenolphthalein as an indicator, stop adding when the solution changes from colorless to light red, then heat at 80-100°C for 2-3h to remove ethanol and water, transfer the obtained precipitate into an ethanol-ether mixed solution and stir for 2-3h, then filter, wash, dry and grind to finally obtain a viscous dispersant.

2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The mass fraction of oleic acid in the oleic acid ethanol solution is 10%, and the concentration of the sodium hydroxide ethanol solution is 0.5 mol / L.

3. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The LiMn X Fe (1-X) The raw materials for preparing the PO4 precursor include a lithium source, a manganese source, an iron source, and a phosphorus source, wherein the value of X is 0.6-0.

8.

4. The lithium iron manganese phosphate positive electrode material according to claim 3, characterized in that: The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate; The manganese source includes one or more of manganese oxides and manganese salts; The iron source includes one or more of iron oxides and iron salts; The phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and diammonium phosphate.

5. The lithium iron manganese phosphate positive electrode material according to claim 4, characterized in that: The LiMn X Fe (1-X) The preparation method of PO4 precursor is: According to Li Mn X Fe (1-X) The lithium source, manganese source, iron source, phosphorus source and deionized water were weighed and put into a grinder to grind them thoroughly. The slurry was taken out and placed in a spray dryer for spray granulation to obtain Li Mn X Fe (1-X) PO4 precursor.

6. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The composite carbon source comprises polyvinyl alcohol and polyacrylonitrile in a mass ratio of 5:

2.

7. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The conductive agent is Super-P.

8. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The binder is polyvinylidene fluoride.

9. A method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Li Mn X Fe (1-X) The PO4 precursor, the composite carbon source and part of the viscous dispersant are added to deionized water in proportion and ultrasonically vibrated for 1-2 hours, and then filtered, dried and ground to obtain a mixture; S2: Place the mixed material in a sintering furnace, sinter at 200°C for 2h in a nitrogen atmosphere, then heat to 650-750°C for 4-5h, cool to room temperature and grind to obtain modified Li Mn X Fe (1-X) PO4; S3: Modified Li Mn X Fe (1-X) PO4, conductive agent, binder and remaining viscous dispersant are mixed evenly, and the obtained black slurry is the lithium manganese iron phosphate positive electrode material.

10. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 9, characterized in that: The usage ratio of the viscous dispersant in step S1 and step S3 is 3:2.